Flavonoids from green propolis of the Northeastern Brazilian Caatinga Mimosa tenuiflora (Willd.) Poir.: A chemotaxonomic aspect - Son, Ninh The; Ribeiro, Victor Pena; Bastos, Jairo Kenupp (Biochemical systematics and ecology, 2022)
The phytochemical study of the hydroethanolic extract of green propolis produced by Apis mellifera in the Northeastern Brazilian Caatinga from Mimosa tenuiflora led to the isolation of sixteen flavonoids, including eleven flavonols 1–11, four flavanones 12–15, and one prenylated flavanone 16. It is the first time they were isolated from the green propolis of Caatinga M. tenuiflora. Flavonols 2–3, and 5–11, and flavanones 14–16 were first isolated from the genus Mimosa related materials, as well as ermanin (2), axillarin (5), eriodictyol 5-O-methyl ether (13), and 5,4′-dihydroxy-6,7-dimethoxyflavanone (14) have never been observed in the family Fabaceae related materials before. HPLC analysis of the hydroalcoholic extracts confirmed M. tenuiflora as the primary botanical source of Caatinga green propolis. Chemotaxonomic significance is discussed in detail. •Chemical constituents were isolated from green propolis of Caatinga Mimomsa tenuiflora for the first time.•Flavonoids are characteristic in Caatinga green propolis from M. tenuiflora.•Flavonols 5–11, and flavanones 14–16 were isolated from the genus Mimosa-for the first time.•Compounds 2, 5, 13, and 14 were detected in the family Fabaceae for the first time.